ANALYZING AMERICAN POPULAR CULTURE PRODUCTS TO EXPLORE CULTURAL VALUES - Imelda Simorangkir (Deiksis, 2014)
Language and culture are two parts of cannot be separated each other, because culture is in language. The other side, to study English language as a foreign language in Indonesia, as same as study the English’s culture.To understand the culture is means to make a communication be fluently between the speakers and make the effective communication because culture as a basic of communication. To communicate is not only talk about the understanding of linguistic, but must understand about the paralanguage include kinesics, tone, the characteristic of sound, gesture and the expression of face that we can see when the interaction by communicate is happen. By the growing of America, the America culture become a means for the English students, especially for the young generation in many countries like the people in Indonesia, the table manner, relationship, and the life style become the size of somebody status. This life style become the growing reflection of somebody that have been followed by the people in many countries in the world, and this life style become a symbol of individual social status. The electronic media such as television, film, etc that have been successed to make the students of Indonesia bring the America-English and their life style be popular. Key words: Languange, culture, communication, social status.